Field guide to the large and medium-sized mammals of Pakistan - Roberts, T.J. (Oxford University Press, 2005)
Tom Roberts' first definitive account of the mammals of Pakistan in 1977 was brought up to date and revised in 1997. The present book on the large mammals of Pakistan is a condensed version of the 1997 edition and is modeled on the modern field guide format, with emphasis on identification and illustration of each species found in the country. This field guide covers 65 species, with detailed life history accounts and individual photographs/pen and ink drawings of the large and medium-sized mammals of Pakistan. The book also examines how modernization has affected the mammals' environment and creates a better awareness of Pakistan's natural wildlife heritage that is in imminent danger of being lost to mankind